Influence of Entrepreneurial Self-Efficacy on Entrepreneurial Continuance Intention through Opportunity Recognition and Fear of Failure among Generation Z Student Entrepreneurs in Surabaya - Sherly Evelyn Winoto; Metta Padmalia (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study investigates the influence of Entrepreneurial Self-Efficacy (ESE) on Entrepreneurial Continuance Intention (ECI) among Generation Z student entrepreneurs in Surabaya, with Opportunity Recognition (OR) and Fear of Failure (FOF) serving as mediating variables. Methodology: A quantitative research design was employed using a survey method. Data were collected from Generation Z student entrepreneurs aged 17–28 years who actively run businesses in Surabaya. The data were analyzed using SmartPLS to test direct and indirect relationships among variables. Results: The findings indicate that Entrepreneurial Self-Efficacy has a positive and significant effect on Entrepreneurial Continuance Intention and Opportunity Recognition, while negatively affecting Fear of Failure. Opportunity Recognition positively influences Entrepreneurial Continuance Intention, whereas Fear of Failure has a negative effect. Both mediating variables partially mediate the relationship between Entrepreneurial Self-Efficacy and Entrepreneurial Continuance Intention. Findings: Entrepreneurial Self-Efficacy strengthens opportunity recognition and reduces psychological barriers that hinder entrepreneurial continuity among student entrepreneurs. Novelty: This study integrates enabling and inhibiting psychological mechanisms within a single mediation model, providing empirical evidence from Generation Z student entrepreneurs in Surabaya. Originality: The study provides empirical evidence focusing on Generation Z student entrepreneurs in Surabaya, a context rarely examined in continuance entrepreneurship research. Conclusion: Enhancing self-efficacy and opportunity recognition, while managing the fear of failure, is crucial to supporting student entrepreneurial sustainability. Type of Paper: Quantitative Research Paper.